Pengetahuan dengan Sikap tentang Menyusui : Studi pada Mahasiswa Tingkat Awal Jurusan Gizi Poltekkes Kemenkes Yogyakarta - Almira Sitasari; Lastmi Wayansari (JURNAL NUTRISIA, 2016)
Background: One of the key to successful breastfeeding is support from health professionals. Students of Politeknik Kesehatan Kemenkes Yogyakarta is a prospective health workers who will spearhead the success of exclusive breastfeeding program. Objective: To determine the relationship between knowledge and attitudes about breastfeeding in first year students of Students of Politeknik Kesehatan Kemenkes Yogyakarta Methods: An observational study with cross sectional study design. Scores of attitude and knowledge of breastfeeding was assessed from the structured and backtranslationed questionnaire Results: This study was followed by 74 respondents. A total of 98.6% of respondents are women. 51.35% are students of undergraduate level. More than 90% of respondents could answer the question of exclusive breastfeeding, dietary intake of nursing mothers, and the benefits of breast-feeding points. Most respondents did not answer breastfeeding challenges point. A positive attitude also shown at the same points of knowledge items. Meanwhile, negative attitude was also shown at breastfeeding challenges items. Spearman correlation results suggest a link between knowledge and attitudes about breastfeeding at the first-year students majoring in nutrition of Politeknik Kesehatan Yogyakarta (P <0.05, r = 0.245) Conclusion: There is a relationship between knowledge and attitudes about breastfeeding at the first-year students majoring in nutrition of Politeknik Kesehatan Kemenkes Yogyakarta Keywords : breastfeeding, knowledge, attitude, students